Sistem Informasi Manajemen Aset PT. Citra Putra Kebun Asri Jorong Estate Berbasis Web - Nasrulloh Yusuf, Ahmad (mijournal.org, 2024)
Assets generally state that assets are resources controlled by the company as a result of past events where future economic benefits are expected to be obtained by the company. Company assets originate from transactions or other events that occurred in the past. Companies usually acquire assets through outlays in the form of purchases or self-production. The Head of Administration independently handles asset data collection and is still done manually using Microsoft Excel. Recording of asset items based on space, fields and conditions is not yet in the application, so the admin does not know the exact number of indoor asset items, fields and does not know the condition of asset items, if re-data of indoor asset items, fields and conditions takes a long time, it is necessary development of applications for recording indoor assets, fields and conditions of asset items. This condition can also lead to the possibility of data collection errors and also the length of time in searching for data if needed at any time. Asset Management Information System PT. Citra Putra Kebun Asri Jorong Estate Web-based using MySQL database. The designs used are Entity Relationship Diagrams (ERD), Data Flow Diagrams (DFD), and Flowcharts. The programming language used is Hypertext Preprocessor (PHP). The system development model used is the waterfall model. The functionality test used is Blackbox testing.